2008
DOI: 10.1038/eye.2008.355
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anterior capsule polishing on anterior capsule opacification after cataract surgery: a randomized clinical trial

Abstract: Aims To evaluate the effect of anterior capsule polishing on the development of anterior capsule opacification (ACO) in patients undergoing cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 28 publications
(38 reference statements)
2
24
1
5
Order By: Relevance
“…4,5 A surgical strategy for ACO prevention is polishing the inner surface of the anterior capsule, which resulted in significantly less ACO than in eyes with unpolished capsules 3 years after surgery in a prospective bilateral randomized patient-and examiner-masked clinical trial. 18 Another prospective randomized observational double-masked clinical trial 19 comprising 120 eyes of 60 consecutive patients found that ACO was significantly lower at 1 month in cases in which the anterior capsule was polished than in cases in which it was not polished. However, the difference in ACO between the 2 groups was insignificant at 6 months.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 A surgical strategy for ACO prevention is polishing the inner surface of the anterior capsule, which resulted in significantly less ACO than in eyes with unpolished capsules 3 years after surgery in a prospective bilateral randomized patient-and examiner-masked clinical trial. 18 Another prospective randomized observational double-masked clinical trial 19 comprising 120 eyes of 60 consecutive patients found that ACO was significantly lower at 1 month in cases in which the anterior capsule was polished than in cases in which it was not polished. However, the difference in ACO between the 2 groups was insignificant at 6 months.…”
Section: Discussionmentioning
confidence: 98%
“…Anterior capsule polishing or vacuum cleaning of the anterior and posterior capsules was not performed. 35 After the absence of visible lens matter (nucleus and cortex) in the capsular bag was confirmed, the anterior chamber was filled with an ophthalmic viscosurgical device (OVD). The IOL was injected into the bag with an injector without enlarging the main incision.…”
Section: Surgical Techniquementioning
confidence: 99%
“…There are many studies concerning the influence of anterior capsule polishing during surgeries involving the implantation of different IOLs on anterior capsule opacification (ACO), posterior capsule opacification (PCO), and the size of the capsulorhexis opening [11, 13, 14, 17]. However, few studies have assessed the effects of anterior capsule polishing on ELP or the axial position stability of IOL.…”
Section: Discussionmentioning
confidence: 99%